Potensi IUPHHK-HTI Melalui Sistem Wanaternak Dalam Mendukung Swasembada Daging - Johansen Silalahi (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2020)
The food issue is a global issue that is very important in supporting the second goal of sustainable development goals (SDGs) i.e. zero hunger. This research is very important in order to support national food/meat self-sufficiency activities in Indonesia. The purpose of the study was to describe and to examine the potential and opportunities of industrial plantations (IUPHHK-HTI) in supporting the national meat self-sufficiency program. This research was a descriptive approach and it was analyzed qualitatively. The data were obtained from secondary data from institutions and literature studies related to this research topic. Data analysis was carried out after gaining of secondary data and continued to tabulate and to describe them by referring to the research objective. The study was conducted in October 2019 with the nature of desk study. The results showed that the application of national self-sufficiency in beef (beef) with the concept of silvopastura is very potential to be applied in the area of ​​industrial timber plantations (IUPHHK-HTI) from the economic aspect (increasing income/community economy), area aspects (the tendency to increase the area of ​​industrial plantation forests) which is very potential to be integrated with livestock (cattle) because of the relationship of mutualism and funding aspects (potential use of CSR funds) from companies engaged in IUPHHK-HTI. The forestry sector, in this case IUPHHK-HTI, has the potential to support food/meat self-sufficiency with the concept of silvopastura and should be considered for development in IUPHHK-HTI especially those owned by the government for further development to a wider scale. The Ministry of Environmental and Forestry must be even more serious in managing animal husbandry by involving the stakeholders particulary local government and local communities, increasing the role of the IUPHHK-HTI Management Unit with partnership schemes, encouraging CSR activities to productive businesses and having a double impact, and providing incentives for the IUPHHK-HTI permit holders who are successfully carrying out animal or silvopastura in their area. Keywords: IUPHHK-HTI, food, self-sufficiency, meat, potential